Autologous Mesenchymal Stromal Cells Prevent Transfusion-elicited Sensitization and Upregulate Transitional and Regulatory B Cells. Issue 9 (September 2018) - Zhang, Zijian; Wilson, Nancy A.; Chinnadurai, Raghavan; Panzer, Sarah E.; Redfield, Robert R.; Reese, Shannon R.; Galipeau, Jacques; Djamali, Arjang
Abstract : Background: We hypothesized that immunomodulatory properties of mesenchymal stromal cells (MSC) may be considered for desensitization. Methods: Autologous or allogeneic bone marrow derived MSC were infused via tail vein at 0.5 M (0.5 × 10 6 ), 1 M, or 2 M cells/dose on days −2, 3, 6, 9, 12 ( prevention ) or 14, 17, 20, 23, 26 ( treatment ) relative to transfusion in a Brown Norway to Lewis rat model (10 groups total, n = 6 per group). Results: At 4 weeks, pooled analyses demonstrated that autologous and allogeneic MSC were equally effective in reducing IgG1 and IgG2a de novo donor-specific antibody (dnDSA, P < 0.001). Dose-response studies indicated that moderate-dose MSC (5 M total) was most effective in reducing IgG1, IgG2a, and IgG2c dnDSA ( P ⩽ 0.01). Time course studies determined that preventive and treatment strategies were equally effective in reducing IgG1 and IgG2a dnDSA ( P ⩽ 0.01). However, individual group analyses determined that moderate-dose (5 M) treatment with autologous MSC was most effective in reducing IgG1, IgG2a, and IgG2c dnDSA ( P ⩽ 0.01). In this group, dnDSA decreased after 1 week of treatment; regulatory B cells increased in the spleen and peripheral blood mononuclear cells; and transitional B cells increased in the spleen, peripheral blood mononuclear cells, and bone marrow ( P < 0.05 for all). Conclusions: Our findings indicate that autologous MSC prevent transfusion-elicited sensitization and upregulate transitional, and regulatory B cells. Additional studies are needed to determine the biological relevance of these changes after kidney transplantation.